Implementation of Character Education Values in Orphanages (Literature Review) - Merentek, Theo Chanra; Saerang, Hetwi Marselina; Lantang, Dani; Sumual, Shelty Deity Meity (AIBPM Publisher, 2022)
An orphanage is an institution that replaces the role of parents in nurturing, maintaining, caring for, and educating children. This study aims to describe the implementation of character education values, obstacles, and efforts made in orphanages. This study uses a literature review method. The data collection technique used google scholar with the keywords